Twenty-Five Years After the Chi-Chi Earthquake in the Light of Natural Time Analysis - Panayiotis A. Varotsos; Nicholas V. Sarlis; Efthimios S. Skordas; Qinghua Huang; Jann-Yenq Liu; Masashi Kamogawa; Toshiyasu Nagao (Geosciences, 2025)
Almost two years after the devastating 1999 MW7.6 Chi-Chi earthquake, a new concept of time termed natural time (NT) was introduced in 2001 that reveals unique dynamic features hidden behind the time series of complex systems. In particular, NT analysis enables the study of the dynamical evolution of a complex system and identifies when the system enters a critical stage. Since the observed earthquake scaling laws indicate the existence of phenomena closely associated with the proximity of the system to a critical point, here we apply NT analysis to seismicity that preceded the 3 April 2024 MW7.4 Hualien earthquake. We find that in the beginning of September 2023 the order parameter of seismicity exhibited a clearly detectable minimum. Such a minimum demonstrates that seismic electric signal (SES) activity initiated which comprises several low-frequency transient changes of the electric field of the Earth preceding major earthquakes.